Screening for group B Streptococcus in pregnant women: a systematic review and meta-analysis Rastreo de Streptococcus del grupo B en gestantes: revisión sistemática y metanálisis Rastreamento de Streptococcus do grupo B em gestantes: revisão sistemática e metanálise - Mônica Taminato; Dayana Fram; Maria Regina Torloni; Angélica Gonçalves Silva Belasco; Humberto Saconato; Dulce Aparecida Barbosa (Revista Latino-Americana de Enfermagem, 2011)
Infection with Group B Streptococcus (GBS) is considered an important public health problem. It is associated with: Neonatal sepsis, meningitis, pneumonia, neonatal death, septic abortion, chorioamnionitis, endometritis and other perinatal infections. The aim of this study was to determine the best screening strategy for GBS in pregnant women. For this a systematic review and meta-analysis were carried out in the Nursing Department of the Federal University of São Paulo, Cochrane Center, Brazil. Sources used were, EMBASE, LILACS, Medline, list of references, personal communication and the Cochrane library. The criterion for the selection of the studies was; studies which analyze some type of screening for GBS in pregnant women. Independent of the comparator, all analyses were in favor of a universal screening program for reducing the incidence of neonatal sepsis. The evidence obtained in this study suggests that the strategy of universal screening of pregnant women associated with the use of prophylactic antibiotics is safe and effective. La infección por Streptococcus del grupo B (GBS) es considerada un importante problema de salud pública. Los estreptococos están asociados a: sepsis neonatal, meningitis, neumonía, muerte neonatal, aborto séptico, corioamnionitis, endometritis y otras infecciones perinatales. El objetico del estudio fue determinar la mejor estrategia de rastreo de GBS en gestantes. Se trata de una revisión Sistemática con Metanálisis. Fue realizada en el Departamento de Enfermería de la Universidad Federal de Sao Paulo, Centro Cochrane de Brasil. Se utilizaron las siguientes fuentes: EMBASE, LILACS, Medline, lista de referencias bibliográficas, comunicación personal y Cochrane Library. Como criterio para la selección de los estudios, se escogieron los que analizaron algún tipo de rastreo para GBS en gestantes. Independientemente del comparador, todos los análisis fueron favorables al programa de screening universal para la reducción de la incidencia de sepsis neonatal. Las evidencias obtenidas en el estudio sugieren que la estrategia de screening universal para las gestantes asociado al uso de antibióticos profilácticos es segura y efectiva. A infecção por Streptococcus do grupo B (GBS) é considerada importante problema de saúde pública. Está associada à sepse neonatal, meningite, pneumonia, óbito neonatal, aborto séptico, coriomnionite, endometrite e outras infecções perinatais. O objetivo deste estudo foi determinar a melhor estratégia de rastreamento de GBS em gestantes. Como método usou-se a revisão sistemática com metanálise. A pesquisa foi realizada no Departamento de Enfermagem/Universidade Federal de São Paulo/Centro Cochrane do Brasil. Para a busca usaram-se as fontes Embase, LILACS, MEDLINE, lista de referências bibliográficas, comunicação pessoal e Cochrane Library. Usaram-se, como critério de seleção, os estudos que analisaram algum tipo de rastreamento para GBS em gestantes. Independente do comparador, os resultados apontam que todas as análises foram favoráveis ao programa de screening universal para a redução da incidência de sepse neonatal. Pode-se concluir que evidências obtidas no estudo são sugestivas de que a estratégia de screening universal para as gestantes, associada ao uso de antibiótico profilático, é segura e efetiva.